The Influence of Attitude Toward Money, Locus of Control, Financial Self-Efficacy and Self-Control on Financial Management Behavior - Welly Chandra; Ary Satria Pamungkas (International Journal of Application on Economics and Business, 2023)
The aim of this study was to determine the role of Attitude toward Money, Locus of Control, Financial Self-Efficacy and Self-Control in explaining Financial Management Behavior among workers that use E-commerce and live in Jakarta. The samples used in this study are workers that use E-commerce and live in Jakarta. This study collected 208 samples who are workers that use E-commerce and live in Jakarta. The respondents selected by using convenience sampling method. This research used Partial Least Square-Structural Equation Modeling (PLS-SEM) to analyze data. The result of this study indicated that Attitude toward Money, Locus of Control, Financial Self-Efficacy and Self-Control has positive influence on explaining Financial Management Behavior.